Escola de tempo integral: um estudo da dimensão subjetiva com pais e alunos - Lemos, Ruth Willna Ferreira de (2012)
The present work aims to develop na understanding about the subjective dimension of the ecational process in a full time school, in other words, to meet the subjective aspects made by those individuals Who live this experience. For this, researches were made in the statemens of parents and students of and students, elements that make up the meanings (senses) on Full-Time school. This research was based on restlessness of observing the inequality educational context ok our country and bringing support to the proposal of Full-Time Education and the program Mais Educação . The theorist used in this research was the sócio-historic psychology, which has as its starting point the Idea tha all human phenomena are produced in the historical processo of social life formation, thus converging with the prospect of Full-Time Education. The participants were three studens in the 8th year of na elementary full-time school in the city of Jo~so Pessoa in Paraíba, and two parents of students at the respective school. Specifically for this Project were developed semi-structured inerviews with both parents and students, held by the researcher. Data were generated from the analysis of the speeches, by the method of categorization.The results allowed us to understand that there is no clarity on how they view the changes in terms of what would be the quality of educacion in school. Their senses about full-time school are that more time in school protects and provides a better learning for students, when copared to other schools. However, the vision seems abstract thesesubjects with regard to the proposal for Full-Time Education